The schoolboys' revenge: how the golden line entered classical scholarship. (29th January 2020) - Mayer, Kenneth
Abstract: The golden line, a Latin versification exercise in British classrooms since at least 1612, appears to have no basis in the classical tradition. It was resisted by the academy for decades — if not centuries. Then, as Latin versification ceded its central role in schools and universities, resistance withered. New generations of scholars had never encountered the golden line as a composition exercise, and they saw instead the golden line as a critical tool for interpreting Latin poetry. After the 1950s, the golden line spread to Italy, Spain, Belgium, Germany, France, and beyond. A classroom exercise helped shape scholarship worldwide. Yet the golden line is an even more striking example of scholarship from below, because it thrived due to its documented appeal to the students who identified and composed them. From the 1600s until today, students have expressed pride and joy in identifying and composing golden lines. Student preferences often shape pedagogical canons and classroom practice, but the golden line went still further. Today, Latinists worldwide analyse poets of the classical canon by counting and discussing their golden lines. Student preferences for a school exercise have changed not only pedagogy but scholarly practice.